Flat Absorber Black PEO coatings on Ti6Al4V for spacecraft thermal control application. Issue 23 (1st December 2022) - Madhuri, Deyyala; Ghosh, Rahul; Hasan, Mohammed Adnan; Dey, Arjun; Pillai, Anju M.; Angamuthu, Murugan; Anantharaju, K.S.; Rajendra, A.
Abstract: Black appearance and flat absorber, i.e., high solar absorptance (αs ) and high IR emittance (εir ) surfaces, are essential for optical benches and optical mounts in astronomical and scientific payloads/spacecraft. Generally, these optical benches and optical mounts are fabricated by Ti6Al4V alloy due to its superior mechanical and thermal properties. However, bare Ti6Al4V is restricted for spacecraft thermal control applications due to its low emittance, intermediate absorptance, and moderate corrosion resistance behaviors. Hence, plasma electrolytic oxidation (PEO) technique was utilized to develop black and flat absorber coatings on bare Ti6Al4V alloy. Sodium silicate (SS), sodium hypophosphate (SHP), and potassium fluoride (KF) were used for the preparation of the electrolytic bath. Process parameters such as current density, duty cycle, frequency, the concentration of electrolytes, and duration were judiciously altered to get uniform PEO coatings with the flat absorbing property. Six numbers of PEO coatings were finally chosen for further in-depth characterizations as they showed adequate flat absorbing property. The phase composition, microstructure, roughness, and wettability of those PEO coatings were thoroughly studied by X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), profilometry, and water contact angle measuring techniques, respectively. Thermo-optical properties viz., εir and αs of the coatings were recorded by portable IR emissometer and solar reflectometer, respectively, and electrical sheet resistance was measured by two probe method. The Nanomechanical properties of the coatings, such as modulus (E) and nanohardness (H), were evaluated by the nanoindentation technique. The PEO coatings were also investigated with respect to potentiodynamic polarization to investigate corrosion resistance of the PEO coatings. The highest εir value of PEO coating was achieved as 0.87 for a 20% duty cycle with a combination of SS + SHP electrolytes, while the maximum αs value was achieved as 0.83 for the same 20% duty cycle with a combination of SS + SHP + KF electrolytes.